2020
DOI: 10.3390/ijms21072542
|View full text |Cite
|
Sign up to set email alerts
|

The Vascular Involvement in Soft Tissue Fibrosis—Lessons Learned from Pathological Scarring

Abstract: Soft tissue fibrosis in important organs such as the heart, liver, lung, and kidney is a serious pathological process that is characterized by excessive connective tissue deposition. It is the result of chronic but progressive accumulation of fibroblasts and their production of extracellular matrix components such as collagens. Research on pathological scars, namely, hypertrophic scars and keloids, may provide important clues about the mechanisms that drive soft tissue fibrosis, in particular the vascular invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 111 publications
0
22
0
Order By: Relevance
“…Multiple lines of evidence show that the blood vessels are deranged in cutaneous pathological scars. 4,5 In particular, they are very dense at the inflamed periphery of the pathological scar yet largely absent in the inactive center. 6,7 In keloid patients, the systemic balance between proangiogenic factors and anti-angiogenic factors is distorted, as indicated by the altered circulating levels of vascular endothelial growth factor (VEGF), endothelial progenitor cells (EPCs), and endostatin, as follows.…”
Section: Factorsmentioning
confidence: 99%
“…Multiple lines of evidence show that the blood vessels are deranged in cutaneous pathological scars. 4,5 In particular, they are very dense at the inflamed periphery of the pathological scar yet largely absent in the inactive center. 6,7 In keloid patients, the systemic balance between proangiogenic factors and anti-angiogenic factors is distorted, as indicated by the altered circulating levels of vascular endothelial growth factor (VEGF), endothelial progenitor cells (EPCs), and endostatin, as follows.…”
Section: Factorsmentioning
confidence: 99%
“…Ogawa (2017) suggested that keloids and hypertrophic scars are derived from an abnormal inflammatory reaction in the skin since proinflammatory factors, including IL-1α, IL-1β, IL-6, and TNF-α, are associated with keloid formation. Additionally, disorders of vascular cells can cause pathological scars since inflammation stimulates excessive angiogenesis, endothelial disorder, and vascular hyperpermeability (Huang and Ogawa, 2020). It has been proposed that mechanical tension promotes the dysregulation of cell proliferation and apoptosis during wound healing and may result in keloids and hypertrophic scars (Pozos, 2014;Harn et al, 2019;Ogawa, 2019).…”
Section: Fibrosis Keloids and Hypertrophic Scarsmentioning
confidence: 99%
“…Regarding downregulated circRNAs, morphogenesis of the epithelium showed the highest relevance in GO analyses. It is well known that epithelial cells transform into myofibroblasts and fibroblasts via the epithelialmesenchymal transition (EMT) process (Yuan et al, 2019;Huang and Ogawa, 2020). Chen and the co-workers (Chen et al, 2020) found that circ_0008450 promotes proliferation and processing in human keratinized epithelial cells through the TGF-β/Smad/Runx3 axis.…”
Section: Discussionmentioning
confidence: 99%
“…Keloids are benign skin fibroproliferative tumors unique to humans characterized by aggressive fibroblast proliferation, excessive accumulation of extracellular matrix (ECM) (e.g., collagen I and III), long-term continuous fibrosis, and abnormal inflammatory stimuli (Yan et al, 2021;Zhang et al, 2021). Keloids show various cancer-like features, such as aggressive proliferation beyond the original boundary, lack of spontaneous regression, and vascularization ability (Huang and Ogawa, 2020). As a common clinically challenging disorder, keloid formation generally follows wounding, such as burns, surgery, laceration, or other damage to the dermis (Davies et al, 2021).…”
Section: Introductionmentioning
confidence: 99%